Protected, but Not Included? The Role of Workplace Inclusion for Sexual and Gender Minorities in the Federal Service - Anna Fountain Clark; Jiwon Suh; Kwang Bin Bae (Journal of Public and Nonprofit Affairs, 2022)
The public workplace has traditionally been conceived of in heteronormative and cisnormative terms, wherein heterosexuality, the gender binary, and opposite-sex relationships are presumed and institutionalized in both word and deed. Recent policy changes and public opinion shifts regarding lesbian, gay, bisexual, and transgender individuals have placed an onus on employers to develop means to include sexual and gender minorities in the overall organizational culture and improve LGBT individuals’ workplace experiences. Using multilevel data analysis, this study focuses on how LGBT federal workers’ perceptions of inclusion at the agency, supervisory, and work unit levels affect their job satisfaction. The results indicate that LGBT employees’ inclusion perceptions play a moderating role between their sexual or gender minority identities and individual job satisfaction. The findings suggest that interventions aimed at developing an inclusive culture that reduces or eliminates traditional heteronormativity and cisnormativity, both agency-wide and at separate organizational levels, may improve job satisfaction among LGBT workers.